Knowledge Transfers from Multinational to Domestic Firms: Evidence from Worker Mobility. A Replication Study of Poole (Review of Economics and Statistics, 2013) - Stefanie Haller; Eoin T. Flaherty; Ragnhild Balsvik (Journal of Comments and Replications in Economics (JCRE), 2023)
This paper replicates Poole (2013) using comprehensive Norwegian and Irish register data. Our results largely confirm the evidence documented in Poole for Brazil which suggests that when workers leave multinationals and are rehired at domestic establishments, the wages of their new coworkers who have already been present in the establishment increase. However, unlike suggested in the original article there is little indication that these spillovers differ in a statistically significant way across various dimensions of heterogeneity for any of the three countries.
https://doi.org/10.15456/j1.2023325.1540223821
Keywords: F23; F61; J31; 330; Multinational Firms; Wage Spillovers; Worker Mobility; Replication